B22 Normalisation Of Aberrant P75NTR Levels Prevents Hippocampal Synaptic And Cognitive Deficits And Ameliorates Cortico-striatal Dysfunction In Huntington Disease. (17th September 2014) - Brito, VI; Giralt, A; Enriquez-Barreto, L; Puigdellívol, M; Suelves, N; Morales, M; Martín, ED; Alberch, J; Ginés, S
Abstract : Huntington's disease (HD) patients and mouse models show learning and memory impairment before the onset of motor symptoms. These cognitive impairments are thought to be caused by altered synaptic plasticity and dendritic spine deficits. However the molecular mechanisms underlying these changes are still poorly understood. Among several factors it is well known that BDNF and its receptors, TrkB and p75NTR play a crucial role in synaptic plasticity. In this study we aim to elucidate whether p75NTR participates in the reduced synaptic plasticity associated with cognitive and motor impairments in HD pathology. Previous data from our group demonstrated increased levels of p75NTR in the striatum of HD mice as well as in the putamen of HD patients. Now we extended this data by showing increased p75NTR levels in the hippocampus but not in cortex of exon-1 (R6/1) and full-length (HdhQ111) HD mouse models as well as in HD brain. To analyse the role of p75NTR in HD pathology, we have generated double mutant mice (HdhQ7/111; p75NTR+) heterozygous for mutant huntingtin and p75NTR. Normalisation of p75NTR levels in these double mutant mice completely reversed hippocampal cognitive deficits while only partially ameliorated striatal and cortico-striatal deficits. We further confirm these data by specific viral-mediated knock-down of p75NTR in the hippocampus or in the striatum of HdhQ111 knock-in mutant mice. Interestingly, cognitive improvements were related with a reversal of different molecular pathways essential for synaptic plasticity as well as rescue of dendritic spines loss in the hippocampus. These findings demonstrate that p75NTR up-regulation may be differentially implicated in the striatal and hippocampal reduced plasticity associated with cognitive and motor impairments in HD and suggest that modulation of p75NTR or its signalling could represent a therapeutic strategy for the treatment of memory deficits in this neurodegenerative disease.